Nicotine’s Effectiveness in the Isolated Human Nasal Mucosa - Chou, Ying-Liang; Cheng, Li-Hsiang; Liu, Shao-Cheng; Wang, Hsing-Won (ENT Updates, 2026)
Nicotine is a stimulant that affects the ganglia. Similar to capsaicin, it also activates sensory nerves in the airways, which leads to secretion and coughing in human subjects. The nasal mucosa can be exposed to the drug through either nasal or oral administration. The study investigated the effects of nicotine on electrically stimulated contractions of human nasal mucosa, resting tension of human nasal mucosa, and contractions induced by 10−6 M norepinephrine (NE) or 10−6 M methoxamine, a sympathetic mimetic. The purpose was to assess the direct impact of nicotine on human nasal mucosa in an in vitro laboratory setting. The findings demonstrated that the nasal mucosa contracted in a dose-dependent manner upon the addition of methoxamine to the incubation medium. Addition of nicotine at doses of 10−4 M elicited a significant relaxation response to 10–6 M methoxamine-induced mucosal strip contraction. Nicotine could inhibit electrical field stimulation-induced spike contraction and had a negligible effect on the basal tension of the nasal mucosa as the concentration increased. Adding 10−6 M nicotine to the 10−6 M NE-induced contraction, it initially induced a small reduction of the contraction, then it potentiated the contractions. This study demonstrated that high nicotine concentrations had a significant spasmolytic effect via antagonistically binding to α-adrenoceptors. Moreover, people with nasal allergies and stuffy noses who additionally utilize an α-adrenergic agonist nasal spray, oral or smoked nicotine, or both concurrently may not get relief from nasal obstruction.